-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathexercise12.tex
528 lines (454 loc) · 17.9 KB
/
exercise12.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
\documentclass[11pt]{article}
% % \def\hidesolutions{}
\input{header}
\begin{document}
\exsheet{12}{5}{December} % parameters are the number of the session and the day
\begin{exercise}
Consider the following functions with period $T$:
\begin{itemize}
\item A function $f$ with period $T = 1$ such that
\begin{align*}
f(x) =
\left\{\begin{array}{ll}
1 & \text{if } 0 \leq x < 0.5 \\
0 & \text{if } 0.5 \leq x \leq 1
\end{array}\right.
\end{align*}
\item A function $g$ with period $T = 2\pi$ such that
\begin{align*}
g(x) =
\left\{\begin{array}{ll}
x & \text{if } 0 \leq x < \pi \\
2\pi - x & \text{if } \pi \leq x \leq 2\pi
\end{array}\right.
\end{align*}
\item A function $h$ with period $T = 1$ such that
\begin{align*}
h(x) = -x \text{ if } 0 \leq x < 1.
\end{align*}
\end{itemize}
Find the Fourier coefficients of the Fourier series of these functions.
\textit{You can use the Fourier series seen in the lecture to get the coefficients.}
\end{exercise}
\begin{solution}
\begin{itemize}
\item As seen in the lecture we know the Fourier coefficients of a square wave,
\[
l(x)= \begin{cases}1, & \text { if } 0 \leq x<0.5 \\ -1, & \text { if } 0.5 \leq x<1\end{cases},
\]
are given by:
\[
a_n = 0\quad \text{for } n \geq 0, \quad b_n = \begin{cases}0, & \text { if n is even} \\ \frac{4}{n\pi}, & \text{ if n is odd}\end{cases}
\]
We can express the function $f(x)$ in terms of $l(x)$ as follows:
\[
f(x) = \frac{1}{2} + \frac{1}{2}l(x)
\]
therefore the Fourier coefficients of $f$ are given by:
\[
a_n = \begin{cases} 1, & \text { if n} = 0 \\0,& \text{ if n }>0\end{cases}, \quad b_n = \begin{cases}0, & \text { if n is odd} \\ \frac{2}{n\pi}, & \text{ if n is even}\end{cases}
\]
\item As seen in the lecture we know the Fourier coefficients of a triangle wave,
\[
m(x)= \begin{cases} 2 x, & \text { if } 0 \leq x<0.5 \\ 2(1-x), & \text { if } 0.5 \leq x<1\end{cases}
\]
are given by:
\[
a_0 = 1, \quad a_n = \begin{cases}-\frac{4}{n^2\pi^2}, & \text { if n is odd} \\ 0, & \text{ if n is even}\end{cases}, \quad b_n = 0 \text{ for } n > 0
\]
We can express the function $g(x)$ in terms of $m(x)$ as follows:
\[
g(x) = \pi m(\frac{x}{2\pi})
\]
therefore the Fourier coefficients of $g$ are given by:
\[
a_0 = \pi, \quad a_n = \begin{cases}-\frac{4}{n^2\pi}, & \text { if n is odd} \\ 0, & \text{ if n is even}\end{cases}, \quad b_n = 0 \text{ for } n > 0
\]
\item As seen in the lecture we know the Fourier coefficients of a sawtooth wave,
\[
n(x)=x \text { for } 0 \leq x<1
\]
are given by:
\[
a_0 = 1, \quad a_n = 0 \text{ for } n > 0, \quad a_n = -\frac{1}{n\pi} \text{ for } n > 0,
\]
We can express the function $h(x)$ in terms of $n(x)$ as follows:
\[
h(x) = -n(x)
\]
therefore the Fourier coefficients of $h$ are given by:
\[
a_0 = -1, \quad a_n = 0 \text{ for } n > 0, \quad a_n = \frac{1}{n\pi} \text{ for } n > 0,
\]
\end{itemize}
\end{solution}
\begin{exercise}
Explicitly write down the coefficients $a_n$ and $b_n$ and the periods of the following Fourier series:
\begin{align*}
f(x) &= \sum_{n=1}^{\infty} \frac{1}{(2n+1)^2}\sin(2\pi (2n+1) x),
\\
g(x) &= \sum_{n=1}^{\infty} \frac{(-1)^n}{(2n-1)^3}\cos(2\pi (2n-1) x),
\\
h(x) &= \frac \pi 3 + \sum_{n=1}^{\infty} \frac{(-1)^{n+1}}{n^2}\cos(\pi n x).
\end{align*}
Determine the Fourier coefficients of the derivatives of those functions.
\end{exercise}
\begin{solution}
\begin{itemize}
\item We substitute $m = 2n+1$ to obtain
\[
f(x) = \sum_{\substack{m=3\\m \text{ is odd}}}^{\infty} \frac{1}{m^2}\sin(2\pi m x),
\]
therefore the Fourier coefficients are given by
\[
a_m = 0 \text{ for } m \geq 0, \quad b_m = \begin{cases}\frac{1}{m^2}, & \text { if m is odd and }m \geq 3 \\ 0, & \text{ otherwise } \end{cases}
\]
and the period is $T = 1$. The derivative of $f(x)$ is given by:
\[
f'(x) = \sum_{\substack{m=3\\m \text{ is odd}}}^{\infty} \frac{2\pi}{m}\sin(2\pi m x),
\]
therefore the Fourier coefficients of the derivative of $f(x)$ are given by
\[
b_m = 0 \text{ for } m \geq 0, \quad a_m = \begin{cases}\frac{2\pi}{m}, & \text { if m is odd and }m \geq 3 \\ 0, & \text{ otherwise } \end{cases}
\]
\item We substitute $m = 2n-1$ to obtain
\[
g(x) = \sum_{\substack{ m=1 \\ m \text{ is odd}}}^{\infty} \frac{(-1)^{\frac{m+1}{2}}}{m^3}\cos(2\pi m x),
\]
therefore the Fourier coefficients are given by
\[
b_m = 0 \text{ for } m >0, \quad a_m = \begin{cases}\frac{(-1)^{\frac{m+1}{2}}}{m^3}, & \text { if m is odd and }m \geq 1 \\ 0, & \text{ if m is even and } m \geq 1\\ 0 & \text{ if } m = 0 \end{cases}
\]
and the period is $T = 1$. The derivative of $g(x)$ is given by:
\[
g'(x) = \sum_{\substack{m=1\\m \text{ is odd}}}^{\infty} -\frac{2\pi (-1)^{\frac{m+1}{2}}}{m^2}\sin(2\pi m x),
\]
therefore the Fourier coefficients of the derivative of $g(x)$ are given by
\[
a_m = 0 \text{ for } m \geq 0, \quad b_m = \begin{cases}-\frac{2\pi (-1)^{\frac{m+1}{2}}}{m^2}, & \text { if m is odd and }m \geq 1 \\ 0, & \text{ if m is even and } m \geq 1\\ 0 & \text{ if } m = 0 \end{cases}
\]
\item
the Fourier coefficients are given by
\[
b_n = 0 \text{ for } n >0, \quad a_n = \begin{cases}\frac{2\pi}{3}, & \text { if }n = 0 \\ -\frac{(-1)^n}{n^2}, & \text{ if } n > 1 \end{cases}
\]
and the period $T = 2$. The derivative of $h(x)$ is given by:
\[
h'(x) =\sum_{n=1}^{\infty} -\frac{\pi(-1)^{n+1}}{n}\sin(\pi n x),
\]
therefore the Fourier coefficients of the derivative of $h(x)$ are given by
\[
a_n = 0 \text{ for } n \geq 0, \quad b_n = -\frac{\pi(-1)^{n+1}}{n},\quad \text{for }n > 0
\]
\end{itemize}
\end{solution}
\begin{exercise}
Let \( f(x) \) be a periodic function with period \( T \), represented by its Fourier series:
\begin{align*}
f(x) = \frac{a_0}{2} + \sum_{n=1}^\infty \left( a_n \cos\left(\frac{2\pi n x}{T}\right) + b_n \sin\left(\frac{2\pi n x}{T}\right) \right).
\end{align*}
As explained in the lecture,
\begin{align*}
\int_{x_0}^{x}
f(x)
dx
=
\frac{a_0}{2} ( x - x_0 )
+
\sum_{n=1}^{\infty}
a_n
\int_{x_0}^{x}
\cos\left(\frac{2\pi n x}{T}\right)
dx
+
b_n
\int_{x_0}^{x}
\sin\left(\frac{2\pi n x}{T}\right)
dx
.
\end{align*}
Complete this discussion and find the Fourier series of a function $g(x)$ such that
\begin{align*}
\int_{x_0}^{x} f(x) = c x + g(x)
\end{align*}
for some $c \in \mathbb R$.
\end{exercise}
\begin{solution}
We first compute
\begin{gather*}
\int_{x_0}^x \frac{a_0}{2} \, dt = \frac{a_0}{2} (x - x_0).
\end{gather*}
We integrate the sign and cosine terms, using the fundamental theorem of calculus:
\begin{gather*}
\int_{x_0}^x \cos\left(\frac{2\pi n t}{T}\right) \, dt
=
\frac{T}{2\pi n} \left( \sin\left(\frac{2\pi n x}{T}\right) - \sin\left(\frac{2\pi n x_0}{T}\right) \right).
\end{gather*}
\begin{gather*}
\int_{x_0}^x \sin\left(\frac{2\pi n t}{T}\right) \, dt
=
-\frac{T}{2\pi n} \left( \cos\left(\frac{2\pi n x}{T}\right) - \cos\left(\frac{2\pi n x_0}{T}\right) \right).
\end{gather*}
Combining all terms, the integral \( F(x) \) becomes:
\begin{gather*}
F(x)
=
\frac{a_0}{2} (x - x_0)
+
\sum_{n=1}^\infty
a_n \frac{T}{2\pi n} \left( \sin\left(\frac{2\pi n x}{T}\right) - \sin\left(\frac{2\pi n x_0}{T}\right) \right)
-
b_n \frac{T}{2\pi n} \left( \cos\left(\frac{2\pi n x}{T}\right) - \cos\left(\frac{2\pi n x_0}{T}\right) \right).
\end{gather*}
We rewrite this once again and obtain
\begin{align*}
F(x)
&
=
\frac{a_0}{2} x
-
\frac{a_0 x_0 }{2}
+
\sum_{n=1}^\infty
\left(
(-a_n) \frac{T}{2\pi n} \sin\left(\frac{2\pi n x_0}{T}\right)
+
b_n \frac{T}{2\pi n} \cos\left(\frac{2\pi n x_0}{T}\right)
\right)
\\&\qquad\qquad\qquad\qquad
+
\sum_{n=1}^\infty
(-b_n) \frac{T}{2\pi n} \cos\left(\frac{2\pi n x}{T}\right)
+
a_n \frac{T}{2\pi n} \sin\left(\frac{2\pi n x}{T}\right)
.
\end{align*}
We thus obtain $c = \frac{a_0}{2}$ and the Fourier coefficients of the function $g$:
\begin{align*}
\frac{A_0}{2} &:= -\frac{a_0 x_0 }{2}
+
\sum_{n=1}^\infty
\left(
(-a_n) \frac{T}{2\pi n} \sin\left(\frac{2\pi n x_0}{T}\right)
+
b_n \frac{T}{2\pi n} \cos\left(\frac{2\pi n x_0}{T}\right)
\right)
\\
A_n &:= (-b_n) \frac{T}{2\pi n}
\\
B_n &:= a_n \frac{T}{2\pi n}
\end{align*}
This completes the discussion.
\end{solution}
\begin{exercise}
Suppose that $f : \bbR \rightarrow \bbR$ and $g : \bbR \rightarrow \bbR$ are functions.
Recall that a function is called \textit{even} if
\begin{align*}
f(-x) = f(x)
\end{align*}
and \textit{odd} if
\begin{align*}
f(-x) = - f(x)
\end{align*}
\begin{itemize}
\item Show that if $f$ and $g$ are both odd or both even, then $fg$ is even
\item Show that if one of $f$ and $g$ is odd and the other is even, then $fg$ is odd.
\item Show that the only function that is both odd and even has constant value zero.
\end{itemize}
\end{exercise}
\begin{solution}
\begin{itemize}
\item If $f$ and $g$ are both even, then
\begin{align*}
f(-x)g(-x) = f(x)g(x),
\end{align*}
and if both are odd, then
\begin{align*}
f(-x)g(-x) = (-1)^{2} f(x)g(x) = f(x) g(x),
\end{align*}
so $fg$ must be an even function.
\item
Suppose that $f$ is even and that $g$ is odd. Then
\begin{align*}
f(-x) g(-x) = f(x) g(-x) = - f(x)g(x),
\end{align*}
showing that $fg$ is an odd function. The same is true if we switch the role of $f$ and $g$.
\item
Suppose that $f$ is both odd and even. Then
\begin{align*}
f(x) = f(-x) = -f(x)
\end{align*}
for each $x \in \bbR$. But the only number that equals its negative is zero. So $f(x) = 0$ for each $x$.
\end{itemize}
\end{solution}
\begin{exercise}
Compute the Fourier transform of the function
\begin{gather*}
f(x) = \left\{\begin{array}{ll}
x & \text{ if $0 \leq x < 1$ }
\\
0 & \text{ otherwise }
\end{array}\right.
\end{gather*}
You can either directly use the complex exponential, or you can express it in terms of the sine and cosine function.
(Interpretation: the function $f(x)$ describes a localized signal: it is zero at $x=0$, then it rises linearly up to $1$, and then it jumps back to zero and remains zero from there on. The signal is not periodic.)
\end{exercise}
\begin{solution}
We write down the solution in two different ways, either using the complex exponential directly, or writing it as a sum of sine and cosine.
\begin{align*}
\mathfrak{F}(f)(\alpha)&=\frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x) e^{-i \alpha x} d x\\
&=\frac{1}{\sqrt{2 \pi}} \int_{0}^{1} x e^{-i \alpha x} d x\\
&=\frac{1}{\sqrt{2 \pi}} \left[ \frac{x}{-i\alpha} e^{-i \alpha x} \right]_0^1 - \frac{1}{\sqrt{2 \pi}} \int_{0}^{1} \frac{1}{-i\alpha} e^{-i \alpha x} d x\\
&=\frac{1}{\sqrt{2 \pi}} \left[ \frac{x}{-i\alpha} e^{-i \alpha x} \right]_0^1 + \frac{1}{\sqrt{2 \pi}} \int_{0}^{1} \frac{1}{i\alpha} e^{-i \alpha x} d x\\
&=\frac{1}{\sqrt{2 \pi}} \left[ \frac{x}{-i\alpha} e^{-i \alpha x} \right]_0^1 + \frac{1}{\sqrt{2 \pi}} \left[ \frac{1}{\alpha^2} e^{-
i \alpha x} \right]_{0}^1\\
&=\frac{1}{\sqrt{2 \pi}} \frac{1}{-i\alpha} e^{-i \alpha } + \frac{1}{\sqrt{2 \pi}} \left( \frac{1}{\alpha^2} e^{-i \alpha} -\frac{1}{\alpha^2}\right)\\
&=\frac{1}{\sqrt{2 \pi}}\left( \frac{i}{\alpha} e^{-i \alpha } + \frac{1}{\alpha^2} e^{-i \alpha} -\frac{1}{\alpha^2}\right)\\
&=\frac{1}{\sqrt{2 \pi}}\left( \frac{i}{\alpha} \cos\alpha + \frac{1}{\alpha} \sin\alpha + \frac{1}{\alpha^2} \cos\alpha - \frac{i}{\alpha^2} \sin\alpha -\frac{1}{\alpha^2}\right)\\
\end{align*}
Next we do it in terms of sine and cosine functions.
\[
\begin{aligned}
\mathfrak{F}(f)(\alpha)&=\frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x) e^{-i \alpha x} d x\\
&=\frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x)(\cos \alpha x - i\sin\alpha x) d x\\
& = \frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x) \cos\alpha x d x - i\frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x) \sin\alpha x d x
\end{aligned}
\]
We evaluate each integral seperately.
\begin{align*}
\int_0^1 x \cos (\alpha x) d x
& =
\left[\frac{x}{\alpha} \sin \alpha x\right]_0^1-\int_0^1 \frac{1}{\alpha} \sin \alpha x d x
\\ &
=\left[\frac{x}{\alpha} \sin \alpha x\right]_0^1+\left[\frac{1}{\alpha^2} \cos \alpha x\right]_0^1
\\ &
=\frac{1}{\alpha} \sin \alpha+\frac{1}{\alpha^2} \cos \alpha-\frac{1}{\alpha^2}
\end{align*}
\begin{align*}
\int_0^1 x \sin (\alpha x) d x
&
=\left[-\frac{x}{\alpha} \cos (\alpha x)\right]_0^1+\int_0^1 \frac{1}{\alpha} \cos (\alpha(x) d x
\\ &
=\left[-\frac{x}{\alpha} \cos (\alpha x)\right]_0^1+\left[\frac{1}{\alpha^2} \sin \alpha x\right]_0^1
\\ &
=-\frac{1}{\alpha} \cos \alpha+\frac{1}{\alpha^2} \sin \alpha
\end{align*}
All together we have:
\begin{align*}
\mathfrak{F}(f)(\alpha)
&
=
\frac{1}{\sqrt{2 \pi}} \int_{-\infty}^{\infty} f(x) e^{-i \alpha x} d x
\\&
=
\frac{1}{\sqrt{2\pi}}\left(\frac{1}{\alpha} \sin \alpha+\frac{1}{\alpha^2} \cos \alpha-\frac{1}{\alpha^2} +i\frac{1}{\alpha} \cos \alpha-i\frac{1}{\alpha^2} \sin \alpha\right)
\end{align*}
\end{solution}
\begin{exercise}
Find the Fourier transform of
\begin{align*}
f(x) = \left\{\begin{array}{ll}
\sin(x) & \text{ if } 0 \leq x \leq 2 \pi
\\
0 & \text{ otherwise }
\end{array}
\right.
\end{align*}
\end{exercise}
\begin{solution}
We try to perform integration by parts
\begin{align*}
\mathcal{F}(f(x))(\alpha)
& =
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
\\ &
=
\frac{1}{\sqrt{2 \pi}}\left[\sin x \frac{e^{-i \alpha x}}{-i \alpha}\right]_0^{2 \pi}
+
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \frac{\cos x}{i \alpha} e^{-\alpha i x} d x
\\ &
=
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \frac{\cos x}{i \alpha} e^{-\alpha i x} d x
\\ &
=
\frac{1}{\sqrt{2 \pi}}\left[\frac{\cos x}{a^2} e^{-i \alpha x}\right]_0^{2 \pi}
+
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \frac{\sin x}{\alpha^2} e^{-i \alpha x} d x
\\ &
=
\frac{1}{\sqrt{2 \pi} \alpha^2}\left(e^{-2 \pi i \alpha}-1\right)+\frac{1}{\alpha^2} \frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
\end{align*}
It seems we have obtained the term that we started with. However,
\begin{align*}
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
=
\frac{1}{\sqrt{2 \pi} \alpha^2}\left(e^{-2 \pi i \alpha}-1\right)+\frac{1}{\alpha^2} \frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
\end{align*}
can be rearranged to
\begin{align*}
\left( 1 - \frac{1}{\alpha^2} \right)
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
=
\frac{1}{\sqrt{2 \pi} \alpha^2}\left(e^{-2 \pi i \alpha}-1\right)
.
\end{align*}
It follows that
\begin{align*}
\frac{1}{\sqrt{2 \pi}} \int_0^{2 \pi} \sin x e^{-i \alpha x} d x
&
=
\left( 1 - \frac{1}{\alpha^2} \right)^{-1}
\frac{1}{\sqrt{2 \pi} \alpha^2}\left(e^{-2 \pi i \alpha}-1\right)
\\&
=
\left( \frac{\alpha^2-1}{\alpha^2} \right)^{-1}
\frac{\left(e^{-2 \pi i \alpha}-1\right)}{\sqrt{2 \pi} \alpha^2}
\\ &
=\frac{\alpha^2}{\alpha^2-1} \frac{\left(e^{-2 \pi i \alpha}-1\right)}{\alpha^2 \sqrt{2 \pi}}
\\ &
=
\frac{\left(e^{-2 \pi i \alpha}-1\right)}{\sqrt{2 \pi}\left(\alpha^2-1\right)}
\end{align*}
which is the desired Fourier transform.
\end{solution}
\begin{exercise}[Extra]
We have introduced the Fourier transform
\begin{align*}
\frakF(f)(\alpha) := \frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty} f(x) e^{-i \alpha x} dx
\end{align*}
Different authors define the Fourier transform alternatively by:
\begin{align*}
\frakF_2(f)(\xi)
:= \int_{-\infty}^{\infty} f(x) e^{-i 2\pi \xi x} dx
,
\quad
\frakF_3(f)(\omega)
:= \int_{-\infty}^{\infty} f(x) e^{-i \omega x} dx
.
\end{align*}
Express $\frakF_{2}(f)$ and $\frakF_{3}(f)$ in terms of $\frakF(f)$.
\end{exercise}
\begin{solution}
Obviously,
\begin{align*}
\frakF_{3}(f)(\omega) = \sqrt{2\pi} \frakF(f)(\omega).
\end{align*}
For the other transformation, we write:
\begin{align*}
\frakF_2(f)(\xi)
&
=
\int_{-\infty}^{\infty} f(x) e^{-i 2\pi \xi x} dx
=
\sqrt{2\pi}
\cdot
\frac{1}{\sqrt{2\pi}}
\int_{-\infty}^{\infty} f(x) e^{-i 2\pi \xi x} dx
=
\sqrt{2\pi}
\cdot
\frakF(f)( 2\pi \xi )
.
\end{align*}
\end{solution}
\end{document}